Personality of the lecturer in training the future teacher - Kregždė, S. (Psichologija, 1982)
The attitude of lecturers towards the profession of the teacher as seen by the students of the Pedagogical Institute is investigated. The method of collective anonymous interview was employed. It has been established according to the estimation of the students that 31 percent of the teachers of the Institute, delivering lectures, conducting seminars and laboratory works highly appreciate the teacher’s profession, 25.5 percent appreciate it positively, 10.5 percent - negatively, and there are 33 percent of lecturers whose attitude the students were unable to indicate. They consider that these lecturers do not try to express their attitude to the subject and to the teacher’s profession. The difference in the attitudes among lecturers of different subject cycles is observed within the limits of 35 percent. On the ground of the revealed tendencies future tasks in the investigation of the problem are pointed out.